Towards sustainable small and medium enterprises (SMEs): awareness and overcoming challenges / Mohamad Hanif Abu Hassan ... [et al.] - Abu Hassan, Mohamad Hanif; Shari, Wahidah; Abd. Wahab, Norazlina; Mohd Ezanee, Adriana Asmaa'; Abdul Wahab, Noor Maimun (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study evaluates sustainability awareness among Malaysian small and medium enterprises (SMEs) and identifies factors and challenges influencing sustainability practices. It involves a descriptive analysis of 200 SME profiles, validated through a focus group discussion (FGD) with authorities. Findings reveal that most respondents are privately owned, have fewer than 50 employees, and operate in trading and services. Sustainability awareness is moderate, requiring improvement for environmental, social, and governance (ESG) goals. Challenges include limited knowledge of environmental regulations, difficulties in community engagement, and resource constraints. Cross-tabulation shows that private ownership, smaller size, Penang location, and trading sector involvement correlate with better ESG performance. Surprisingly, businesses established a decade ago exhibit stronger ESG performance, warranting further study. Thematic analysis highlights diverse sustainability engagement approaches, such as awareness-raising, reporting, enforcement, and seeking recognition. Experts stress the need to educate SME owners on sustainability and advocate for government and financial support. Policymakers and support organizations should assist SMEs in overcoming challenges and fostering sustainable practices.